FVC, FEV1 and FEV1/FVC% in Type 2 Diabetes and Their Relationships with Duration of the Disease - Ali, Md Omar; Begum, Shelina; Begum, Noorzahan; Ali, Taskina; Ferdousi, Sultana; Begum, Afroza (Journal of Bangladesh Society of Physiologist, 2010)
Background: Diabetes mellitus is a chronic debilitating disease affecting various organs including lungs. The magnitude of the complications of this disease is related to its duration. Objective: To observe FVC, FEV1 and FEV1/FVC% in type 2 diabetic patients and their relationship with duration of the disease. Methods: This cross-sectional study was carried out in the Department of Physiology, BSMMU, Dhaka, from July 2007 to June 2008 on 60 type 2 diabetic male patients of age 40-60 years (Group B). For comparison, 30 age and BMI matched apparently healthy non diabetic subjects (Group A) were also studied. Patients were selected from the out patient department of Bangladesh Institute of research on diabetes, endocrine and metabolic diseases. Based on duration of diabetes, diabetic patients were divided into B1 (5-10 years) and B2 (10-20 years). FVC, FEV1 and FEV1/FVC% of all the subjects were measured by a digital microspirometer. Data were analyzed by One way ANOVA test, Unpaired Student's 't' test and Pearson's correlation coefficient test as applicable. Results: Mean of the percentage of the predicted values of FVC and FEV1, were significantly (p<0.001) lower in both those of Gr. B1 and B2 than that in A and were also significantly (p<0.001) lower in Gr. B2 when compared with Gr. B1. Again, FEV1/FVC% was significantly (p<0.01) higher in Gr. B2 than those in Gr. B1 and A whereas this value was lower in Gr. B1 than those of group A but it was not statistically significant. However, FVC and FEV1 showed negative and FEV1/FVC% showed positive correlations with duration of diabetes. All these correlations were statistically non significant. Conclusion: From the result of this study it can be concluded that the ventilatory function of lung may be reduced in type 2 diabetes which may be related to the duration of the disease. Key words: FVC, FEV1, diabetes mellitus DOI: 10.3329/jbsp.v4i2.4178 J Bangladesh Soc Physiol. 2009 Dec;4(2): 81-87